MANUSIA SEBAGAI CITRA ALLAH (Refleksi Teologis Biblis atas Kitab Kejadian) - Dhani Driantoro Gregorius (Bahasa Indonesia, 2019)
Humans are God's creation. He configured to God himself and growing along with the world. In effect, man is the image of God which was given the mandate to rule the earth and set its future. The Fathers ofthe Council's own document on human KV II asserts that man is created in God's image with the ability to know and love his creator God. "Man is destined to rule all creatures in this world. He is the master of all that exists. He mastered and use it while uplift God. But the reality is not always the case. Lately any problems caused by human nature. Therefore, the man who created them from the beginning in the truth, fall into sin. He violated the freedom given by God. Sin is rebellion against God. Rebelling against God is an attitude that shows that God is no longer seen as the foundation of his life. God is no longer seen as a person who should be worshiped.